"Primary Hyperparathyroidism (PHPT) in Children: Two Case Reports and Review of the Literature". (14th April 2021) - Tuli, Gerdi; Munarin, Jessica; Tessaris, Daniele; Buganza, Raffaele; Matarazzo, Patrizia; De Sanctis, Luisa
Abstract : Primary hyperparathyroidism (PHPT) is a rare disorder in children and adolescents. Typical biochemical features are hypercalcemia and hypophosphatemia, but the clinical features can be heterogeneous, and in some cases, symptoms are vague and nonspecific, leading to misdiagnosis or late diagnosis. Herein, we report two cases of PHPT in pediatric age with different presenting symptoms, pain in the foot, and progressive alteration of the gait in the first case and recurrent abdominal pain with emotional lability in the second. Biochemical and radiological assessment confirmed PHPT. Both cases were treated surgically as definitive treatment, but in the second case, previous medical treatment with cinacalcet, a calcimimetic agent, was required to reduce serum PTH and calcium levels. After surgery, despite conventional treatment with calcium and calcitriol, case 1 developed a hungry bone syndrome. The analysis of the MEN-1 (Multiple Endocrine Neoplasia) gene was negative in both cases. A diagnosis of PHPT should be considered when children or adolescents present bone pain with radiological imaging of osteolytic lesion and biochemical feature of hypercalcemia associated with hypophosphatemia. In PHPT, the gold standard treatment is represented by surgery followed by strict postoperative endocrine monitoring to maintain adequate homeostasis of calcium and bone metabolism.